(3GdCSGSjGJ aj GdEOGQI GdeYGUQI (B:s (3efMi fXGej (B/s - (3OQI, YHO GdHGQj GHQGgjes; (3LhOI, eMahX CMeOs ((3YeGf(B: s (3OGQ hGFd(B, s, 2012)
(3JMOjO GdeaGgje GdGSGSjI ddGOGQI , eLGdGJ Mbd GdGOGQI GdeYGUQI h JWhQ GdacQ GdGOGQj (B: (3GdeOGQS GdcdGSjcjI h GdSdhcjI h GdeOGQS h GdGJLGgGJ GdeYGUQI , GdefMi GdfXGej ddGOGQI h GdJWQb Gdi GdJNWjW , GdJfXje , GdJhLjg , GdQbGHI h GdGJUGd , h CNjQG Md GdeTcdGJ h GJNGP GdbQGQGJ(B.s
(3bGFeI GdCTcGd U(B.15s
Keywords: (3GdGOGQIs; (3GdJNWjWs; (3GdQbGHIs